Evaluasi Program Pemuliaan Berdasarkan Parameter Genetik dan Fenotipik Pada Sapi Peranakan Ongole - A. Irianto; Muladno; A. Gunawan (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2021)
The field station of the School for Smallholder Community, Sekaran Village, Kasiman District is one ofthe places for beef cattle development in Bojonegoro Regency. Sekaran Field Station has several breedsof cattle, including Ongole Crossbred. Ongole Crossbreeds have a large population in the Sekaran Schoolfor Smallholder Community with a population of 38%. Evaluation of breeding programs is based ongenetic parameters and can be used to obtain the latest information on the successful implementation ofbreeding programs in a population of livestock. The aim of this study was to evaluate the developmentprogram of Ongole Crossbreed cattle at the Sekaran School for Smallholder Community field stationusing genetic and phenotypic parameters. This study uses a survey method based on questionnaires byconducting interviews with farmers. The data observed were recorded data from 190 heads of OngoleCrossbreeds. The parameters observed were breeding values, genetic and phenotypic correlations, aswell as genetic and phenotypic patterns. The results showed that the highest estimation of breedingvalue in Ongole Crossbred was 5.71 (6 heads) and the lowest was 0.10 (2 heads). The genetic correlationof age at first giving birth, calving distance and empty period ranged from -0.03–0.13. The phenotypiccorrelation of the three reproductive traits ranged from -0.12-0.09. The genetic patterns of age at firstgiving birth, calving distance and empty period were -0.97 months/year, -2.51 days/year and 0.05 days/year, respectively. The phenotypic patterns of the three reproductive traits were 36 months/year, 388days/year and 84 days/year, respectively. Based on the results of the evaluation of the breeding programusing genetic and phenotypic parameters, the development of Ongole Peranakan cattle needs to becontinued by implementing good and digital-based management in order to provide success in the OngoleCrossbred development program at the Sekaran field station of the School for Smallholder Community.